2011
DOI: 10.1091/mbc.e11-05-0405
|View full text |Cite
|
Sign up to set email alerts
|

Hook2 is involved in the morphogenesis of the primary cilium

Abstract: Hook2 partitions between the Golgi apparatus and the centrosome, and its depletion hinders ciliogenesis after mother centriole maturation without Golgi breakdown. Hook2 interacts with PCM1 and Rab8a, and Hook2-depleted cells can be forced to grow primary cilia by overexpressing GFP::Rab8a, indicating that Rab8a acts downstream of Hook2 and PCM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 42 publications
6
66
1
Order By: Relevance
“…The top 50 most prevalent missense SNPs among the 17 samples are presented in Table 2. The highest difference in the allele distribution between our dataset and ESP was estimated for rs2305376 in the gene HOOK2 , encoding a component of the FTS/Hook/FHIP (FHF) complex that has a role in vesicle trafficking and maintenance of centrosome function and is known to interact with the JUN proto-oncogene4041. Interestingly, the variant is predicted to be damaging change due to glycine to arginine substitution (p.G10R), which in addition to its low prevalence in the ESP datasets, is rare to absent in the European population datasets (see Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…The top 50 most prevalent missense SNPs among the 17 samples are presented in Table 2. The highest difference in the allele distribution between our dataset and ESP was estimated for rs2305376 in the gene HOOK2 , encoding a component of the FTS/Hook/FHIP (FHF) complex that has a role in vesicle trafficking and maintenance of centrosome function and is known to interact with the JUN proto-oncogene4041. Interestingly, the variant is predicted to be damaging change due to glycine to arginine substitution (p.G10R), which in addition to its low prevalence in the ESP datasets, is rare to absent in the European population datasets (see Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…Because CCDC41 and IFT20 depend on each other for correct localization, we were not able to test whether CCDC41 plays a role independent of IFT20 in the formation or docking of ciliary vesicles. Previously it was shown that hook homolog 2 (Hook2) accumulates at the centrosome and plays a role in the formation of pericentriolar vesicles (35). However, because it accumulates broadly at the pericentriolar area, Hook2 is unlikely to be sufficient for directing the final docking step of the vesicle to distal appendages.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to point out that satellite-localising PCM1 is generally believed to be important to promote ciliogenesis [19, 20, 109, 113]. The result described earlier clearly indicates a more complex mode of centriolar satellite functions in controlling ciliogenesis because dispersed PCM1 (forming a complex with CEP131/AZI1) is still able to promote or even more potently induce ciliogenesis [58].…”
Section: Cellular Stress Responses and Centriolar Satellite Integritymentioning
confidence: 99%